Measuring quality of life of patients with axial spondyloarthritis for economic evaluation - Hernandez Alava, Monica (2022)
Publisher Copyright: © Author(s) (or their employer(s)) 2022. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.